Perancangan Media Pembelajaran Sejarah Kebudayaan Islam berbasis Android Menggunakan Software Smart App Creator (SAC) - Ansara, Ahmad Dori Pelita; Okra, Riri; Efriyanti, Liza; Musril, Hari Antoni (Yayasan Lembaga Studi Makwa, 2023)
This research aims to produce a learning media for the history of Islamic culture that can increase students' interest in learning. The problem at MAN 1 Bukittinggi was found to be a lack of teacher variation in presenting teaching materials/materials, this was due to the limited media used so that in presenting teaching materials teachers tended to use illustrations depicted in a story using the caramah method. This has an impact on aspects of student understanding, because not all students have the same level of understanding. Teachers should be able to develop a learning atmosphere by presenting material wrapped in attractive media packaging by utilizing contemporary technology such as Android-based media. The research method used is Research and Development (R&D), with a system development model using the Media Development Life Cycle (MDLC) by applying the Luther-Sutopo media development model which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. This research produces a learning media that can be helpful and useful and suitable for use by students and teachers in the eyes of Islamic Cultural History. It was found from the results of validity tests from experts that this product was valid with a value of 0.90, the results of practicality tests carried out by subject teachers showed that this product was declared practical with a value of 0.95, and the results of effectiveness tests from several students showed that this product was very effective with a value of 0.94 . It was concluded that media designed for Android-based Islamic history and culture subjects with Smart App Creator Software can be used validly, practically and effectively in the learning process. Abstrak Penelitian ini bertujuan untuk menghasilkan sebuah media pembelajaran sejarah kebudayaan islam yang dapat meningkatkan minat belajar siswa dalam pembelajaran. Persoalan di MAN 1 Bukittinggi ditemukan bahwa kurangnya vasiasi guru dalam menyajikan bahan/materi ajar, ini disebabkan dengan media yang digunakan masih terbatas sehingga dalam penyempaiann materi ajar guru lebih cendrung menggunakan ilustrasi-ilistrasi yang digambarkan dalam sebuah cerita menggunakan metode caramah. Hal ini berdampak pada aspek pemahaman siswa, karena tidak semua siswa memiliki tingkat pemahamana yang sama. Seyogyanya, guru dapat mengembangkan suasanya belajara dengan menyajikan materi yang dibungkus dengan kemasan media yang menarik dengan memanfaatkan tekonologi kekinian seperti media berbasis android. Metode penelitian yang digunakan adalah Reserch and Develompent (R&D), dengan model pengembangan sistem menggunakan Media Development Life Cycle (MDLC) dengan menerapkan model pengembangan media Luther-Sutopo yang terdiri dari enam tahap yaitu concept, design, material collecting, assembly, testing, dan distribution. Penelitian ini menghasilkan sebuah media pembelajaran yang dapat membantu dan bermanfaat serta layak digunakan oleh siswa dan guru dalam mata Sejarah Kebudayaan Islam. Ditemukan dari hasil uji validitas dari expert menunjukan produk ini valid dengan nilai, 0.90, hasil uji praktikalitas yang dilakukan oleh guru mata pelajaran menunjukan bahwa produk ini dinyatakan praktis dengan nilai 0.95, dan hasil uji efektivitas dari beberapa siswa menunjukan prduk ini sangat efektif dengan nilai 0.94. Disimpulkan bahwa media yang dirancang untuk mata pelajaran sejarah dan kebudayaan islam berbasis android dengan Software Smart App Creator dapat digunakan dengan valid, praktis dan efekti dalam proses pembelajaran.